Assessment of low-loss configurations for efficiency improvement in hybrid modular multilevel converters - Tian, Yumeng (2023)
Hybrid modular multilevel converters (HMMC) address the DC-fault blocking limitations of the half-bridge submodules (HB-SMs) of the standard MMC by combining HB-SMs with full-bridge submodules (FB-SMs). In order to improve the overall conversion efficiency, this article proposes two low-loss configurations for the HMMC. The main improvement in the proposed HMMCs is achieved by the combination of low-loss unipolar and low-loss bipolar SMs in the same arm of the HMMC. It is shown that the simplest structure (LLH1) can reduce the SM losses (switching and conduction losses in an SM) by 30% compared to the HMMC at the cost of limited fault blocking capabilities. The fully controlled structure (LLH2) reduces SM losses by 10% compared to the HMMC, and 30% compared to the FBSM-based MMC. These results represent an increase of 20% over the typical HBSM-based MMC for a converter (LLH2) that can provide fault-blocking capabilities. Assessment of efficiency in both HMMCs is provided over a range of operating conditions both in inverter and rectifier mode from an 800-MVA HVDC system model.